Polyp Detection Rates among Body Mass Index Categories at First Screening Colonoscopy. Issue 1 (January 2017) - Terlizzi, Joseph; Zheng, Andrew; Fuzesi, Sarah; Beekley, Alec; Moleski, Stephanie; Phillips, Benjamin; Isenberg, Gerald; Goldstein, Scott
In the United States, obesity is an epidemic and colorectal cancer is the second deadliest cancer for men and women. A link between obesity and colorectal adenomas and carcinoma has been suggested but not proven. We sought out to determine if obesity was associated with increased rates of polyp formation. All patients undergoing a first screening colonoscopy by one of the participating endoscopists at Thomas Jefferson University Hospital from January 2012 to March 2015 were considered for the study. Their demographics, body mass index (BMI), and colonoscopy findings were recorded at the time of the procedure and prospectively maintained in our database. The final pathologic diagnosis was recorded for each participant as it became available. A total of 758 subjects were included. Of these, 22 per cent had a BMI <25 kg/m 2, 29 per cent had a BMI between 25 and 29.9 kg/m 2, and 49 per cent had a BMI of at least 30 kg/m 2 . Overall, 21.9 per cent of the participants were found to have at least one adenomatous polyp. The polyp detection rates were 24.4 per cent in the group with a BMI less than 25, 20.5 per cent in the overweight group, and 21.6 per cent in the obese group. Our study included 56 super obese individuals with a BMI ≥45 kg/m 2 . About 17.9 per cent of subjects in the super obese group had an adenomatous polyp. There were no differences in the incidence of adenomatous polyps between BMI categories in our study.